PERCEIVED STRESS LEVEL AMONG MADRASAH ‘ALIYAH STUDENTS DURING EXAMINATION WEEK - Akbar, Muhammad Fijar Rotul; Rizki, Achmad; Nur, Maulida (IJISH (International Journal of Islamic Studies and Humanities), 2018)
Academic demands including examinations are found to be the major contributor of stress development among students. Current research is purposed to investigate the prevalence of perceived stress level among Madrasah Aliyah students during examination week. This study was a descriptive and cross-sectional design applying quantitative method for data collection. With respect to the sample, 107 students form Madrasah Aliyah Pasirjambu, Kab. Bandung were proportionally selected from class 10 to class 12. To measure the degree to which particular situations and conditions happening in student’s life are appraised or perceived as stressful situation, Perceived Stress Scale developed by Sheldon Cohen was administered. After which, having gained ethical approval from the foundation board and school director, the data were collected and analyzed using statistical program of SPSS. Result showed that during examination, majority of them were experiencing moderate level of stress accounting for more than 80% and no significant differences of stress level were found with respect to gender, age and study year (class).